Exploitation of Women in Patriarchal Society: A Study of Khaled Hosseini’s A Thousand Splendid Suns (Al-Qamar, 2020)
This article observes that the exploitation of women in the patriarchal society has always been a significant issue in gender and feminist studies. The patriarchal culture inflicts violence upon women; however, women’s acceptance of the patriarchal norms further aggravates their situation. The study argues that the lack of individuality in women makes them bear oppression. The acceptance of myths of male superiority convinces women of their inferior position and they start acting in a feminine way. The study finds that the female characters in Khaled Hosseini’s novel A Thousand Splendid Suns validate and contribute to violence by being submissive and lacking individuality. Additionally, the study uses Simone De Beauvoir’s perspective in The Second Sex (1949) to explain the possible factors responsible for women’s submissive attitude and lack of individuality. The study proposes that the sense of lack of individuality is so deeply rooted in a woman’s mind that no amount of resilience can change her status.
Keywords: Simone De Beauvoir; Feminism; Individuality; Submissiveness; A Thousand Splendid Suns